Problematika Hak Kekayaan Intelektual Di Bidang Merek Bagi Pelaku Usaha Mikro Kecil Menegah - Zulfikri Toguan (UIR Law Review, 2021)
Legal protection for a mark of a place or origin of MSMEs can be done by first registering the mark to obtain legal force. In this case the Office/Agency/Community Organization assists by facilitating MSMEs in terms of socialization and assistance for trademark registration. Law Number 20 of 2016 concerning Marks and Geographical Indications provides improvements to previous laws, especially regarding preventive protection measures, namely registration procedures and registration fees. Brands produced by Indonesian MSMEs can help increase competitiveness in the development of new products. This research is normative or library research method, namely legal research carried out by reviewing and researching library materials in the form of primary legal materials and secondary legal materials. This study concludes: First, the problems in the protection of intellectual property rights in the field of branding for MSME products are due to the understanding of MSME actors on brand rights is still low/shallow so that MSME actors do not register the brand of MSME products. Second, efforts to provide brand protection to the MSME industry are by registering MSME brands and the government makes it easy for MSME industry players to register trademarks.